Silicon-carbon negative electrode material, preparation method thereof and all-solid-state lithium battery

CN122907609APending Publication Date: 2026-10-13SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610913541.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]针对目前的硅碳材料通过包覆碳来进行表面钝化会导致硫化物电解质发生副反应的问题,本申请开发了一种适用于硫化物全固态电池的硅碳材料表面包覆技术,以提高材料对硫化物电解质的相容性,抑制副反应,同时提高材料的离子导电性,从而提高硫化物全固态电池的倍率性能

Benefits of technology

[0018]本申请的有益效果为:本发明提供了一种快离子导体包覆的硅碳材料,该无机快离子导体具有较高的离子电导率(约10-4 S/cm),能够提供锂离子快速传输通道,改善了材料的倍率性能。其次,该快离子导体在负极的稳定性极好,能够有效钝化活性材料,抑制硫化物电解质的持续分解,减少SEI的形成,有利于提高库伦效率和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a silicon-carbon negative electrode material, a preparation method thereof and a full-solid-state lithium battery. The silicon-carbon negative electrode material comprises a porous carbon framework, nano-silicon particles dispersed in the porous carbon framework, a carbon layer deposited on the surface of the porous carbon in which the nano-silicon particles have been dispersed, and a fast-ion-conductor coating layer on the carbon layer, the chemical formula of the fast-ion-conductor being LiZr2(PO4)3 or Li y M x Zr 2‑x (PO4)3, wherein M=Al, La, Ca or Mg, 0<=x<=0.2, 1<=y<=1.4. The silicon-carbon negative electrode material improves the problems of poor ion conduction and poor rate performance of the silicon-carbon negative electrode, improves the compatibility of the coating layer with the sulfide electrolyte, reduces the side reaction, and thus improves the stability during the cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a silicon-carbon anode material, its preparation method, and an all-solid-state lithium battery. Background Technology

[0002] Silicon, with its theoretical specific capacity of 4200 mAh / g (far exceeding graphite's theoretical value of 372 mAh / g), as well as its significant advantages such as low lithium intercalation potential and low cost, has become a core research and development direction for next-generation lithium-ion anode materials. However, silicon-based anodes experience a volume expansion / contraction effect of up to 300% during charge and discharge. This characteristic makes the material extremely prone to pulverization during cycling, leading to its detachment from the current collector and ultimately causing a sharp decline in the battery's electrochemical performance.

[0003] In current commercial applications, silane pyrolysis technology is typically used to deposit nano-silicon particles within porous carbon channels, providing a buffer for silicon volume expansion through the porous structure of the carbon material. However, since the deposited nano-silicon particles are typically smaller than 20 nm and have extremely high surface activity, they must undergo surface carbon coating passivation treatment. This presents a significant drawback in sulfide all-solid-state battery systems, as the carbon coating can induce sulfide electrolyte decomposition, impairing battery performance and failing to meet the application requirements of high-power-density energy storage devices.

[0004] Therefore, how to provide a silicon-carbon material surface coating technology suitable for sulfide all-solid-state batteries to improve the material's compatibility with sulfide electrolytes, while also improving the material's ionic conductivity and the rate performance of all-solid-state batteries, is one of the important technical problems that urgently need to be solved in this field. Summary of the Invention

[0005] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of the claims.

[0006] To address the issue that surface passivation of silicon-carbon materials through carbon coating leads to side reactions in sulfide electrolytes, this application develops a silicon-carbon material surface coating technology suitable for sulfide all-solid-state batteries. This technology improves the material's compatibility with sulfide electrolytes, suppresses side reactions, and enhances the material's ionic conductivity, thereby improving the rate performance of sulfide all-solid-state batteries.

[0007] This application provides a silicon-carbon anode material, comprising a porous carbon framework, nano-silicon particles dispersed in the porous carbon framework, a carbon layer deposited on the porous carbon surface of the dispersed nano-silicon particles, and a fast-ion conductor coating layer on the carbon layer, wherein the fast-ion conductor has the chemical formula LiZr2(PO4)3 or Li y M x Zr 2-x(PO4)3, where M = Al, La, Ca or Mg, 0≤x≤0.2, 1≤y≤1.4.

[0008] In some exemplary embodiments, the amount of the fast ion conductor coating is 0.01 wt% to 10 wt% based on the total weight of the silicon-carbon anode material.

[0009] In some exemplary embodiments, the thickness of the fast ion conductor coating layer is 10 nm to 200 nm.

[0010] A second aspect of this application provides a method for preparing the silicon-carbon anode material described in the first aspect, comprising the following steps: (1) Under an inert atmosphere, the porous carbon material used as the substrate is placed in a deposition furnace and heated to 400℃-800℃; (2) Silicon source gas is introduced into the deposition furnace for vapor phase deposition to form nano-silicon particles; (3) Adjust the temperature to 300℃-800℃, introduce the mixed gas containing carbon source gas and carrier gas into the deposition furnace for surface carbon coating treatment, and cool to room temperature to obtain silicon carbide material. (4) Dissolve lithium salt and phosphate in water according to stoichiometric ratio to obtain a first solution, wherein lithium salt is in excess; dissolve zirconium salt, or zirconium salt and other non-zirconium metal salts in water according to stoichiometric ratio to obtain a second solution; (5) Add the silicon-carbon material obtained in step (3) to the first solution and disperse it by high-speed stirring to obtain a suspension; (6) Add the second solution to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor is calcined in an inert atmosphere and naturally cooled to obtain a silicon-carbon anode material coated with a fast ion conductor.

[0011] In some exemplary embodiments, in step (1), the porous carbon material has a pore size of 1 nm-10 nm and a pore volume of 0.5 cm³. 3 / g-1.2cm 3 / g, specific surface area is 400m² 2 / g-2000m 2 / g.

[0012] In some exemplary embodiments, in step (2), the silicon source gas is selected from one or more of silane, silane, dichlorosilane, and trichlorosilane; The flow rate of the silicon source gas is 0.1 L / min - 50 L / min; and / or The vapor deposition time is 2h-16h.

[0013] In some exemplary embodiments, in step (3), the carbon source gas is one or more of methane, ethane, ethylene, propane, propylene, and propyne; The carrier gas is an inert gas, optionally nitrogen; The volume ratio of the carbon source gas is 1%-10%, and the volume ratio of the carrier gas is 90%-99%. The flow rate of the mixed gas is 0.1 L / min - 50 L / min; and / or The carbon coating time is 0.5h-6h.

[0014] In some exemplary embodiments, in step (4), the lithium salt is one or both of lithium nitrate and lithium hydroxide; The phosphate is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; The zirconium salt is zirconium nitrate or zirconium oxynitrate; The other non-zirconium metal salts mentioned are one or more of aluminum nitrate, lanthanum nitrate, calcium nitrate, calcium nitrite, and magnesium nitrate; and / or The excess lithium salt ranges from 2wt% to 10wt%.

[0015] In some exemplary embodiments, in step (8), the inert atmosphere is one or both of nitrogen and argon; The calcination temperature is 600℃-900℃. Calcination time is 1h-24h, and / or The heating rate is 1℃ / min-10℃ / min.

[0016] A third aspect of this application provides an all-solid-state lithium battery, the all-solid-state lithium battery including a negative electrode, characterized in that the negative electrode includes the silicon-carbon negative electrode material described in the first aspect above.

[0017] In some exemplary embodiments, the calcination temperature is controlled between 600°C and 900°C. If the calcination temperature is too high, more lithium will be lost through volatilization, and the self-diffusion between grains will be enhanced, making it easier to form incomplete island-like coatings; if the calcination temperature is too low, the solid-phase reaction rate will be slow, affecting the crystallinity of the material.

[0018] The beneficial effects of this application are as follows: This invention provides a silicon-carbon material coated with a fast ion conductor, which has a high ionic conductivity (approximately 10). -4The fast ion conductor (S / cm) provides a rapid lithium-ion transport channel, improving the rate performance of the material. Secondly, this fast ion conductor exhibits excellent stability at the negative electrode, effectively passivating the active material, inhibiting the continuous decomposition of sulfide electrolytes, reducing SEI formation, and thus improving coulombic efficiency and cycle performance.

[0019] Other features and advantages of this application will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the application. Other advantages of this application may be realized and obtained by means of the methods described in the description. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application will be described in detail below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.

[0021] The present invention will be further described in detail below with reference to specific examples, but these examples should not be construed as limiting the present invention.

[0022] This invention provides a silicon-carbon anode material, its preparation method, and an all-solid-state lithium battery. The silicon-carbon anode material improves upon the poor ion conductivity and rate performance of silicon-carbon anodes, enhances the compatibility of the coating layer with the sulfide electrolyte, reduces side reactions, and thus improves cycle stability.

[0023] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0024] Example 1 This embodiment provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 5 nm and a pore volume of 0.8 cm³ were prepared. 3 / g, specific surface area 1500m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min; (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Adjust the temperature to 500℃, and pass a mixture of 5% ethylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for surface carbon coating treatment for 2h, and cool to room temperature to obtain silicon-carbon material. (4) Dissolve 0.305g lithium nitrate and 1.455g ammonium dihydrogen phosphate in 300ml of water to obtain the first solution; dissolve 3.621g zirconium nitrate pentahydrate in 200ml of water to obtain the second solution; (5) Add 200g of the silicon-carbon material obtained in step (3) to the first solution and stir at high speed for 1 hour to form a suspension; (6) The second solution is slowly added dropwise to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor was calcined at 850°C for 4 hours under a nitrogen atmosphere with a heating rate of 3°C / min. After natural cooling, LiZr2(PO4)3 coated silicon-carbon anode material was obtained.

[0025] A method for preparing an all-solid-state lithium battery: (1) Electrode preparation: The silicon carbon material obtained above is used as the active material and SBS as the binder. The silicon carbon material:SBS is weighed in a ratio of 98.5wt%:1.5wt% and placed in anisole solvent. After mixing, it is coated on copper foil, dried and rolled to obtain the electrode. (2) Electrolyte pressing: 100 mg Li6PS5Cl was placed in a 10 mm diameter PEEK mold and pressed at 1 t for 1 min to make electrolyte tablets; (3) Cell assembly: Place the electrode on one side of the electrolyte sheet, apply a pressure of 3.6t and hold for 3 minutes. Then place an indium foil with a diameter of 10mm and a thickness of 100μm and a lithium foil with a diameter of 9mm and a thickness of 50μm as the lithium-indium anode on the other side. (4) Overall pressurization: The entire cell is pressurized by 2t and held for 3min to form a solid-state lithium battery.

[0026] After tightening the screws and applying a test pressure of 15 NM, the electrochemical performance was tested.

[0027] Example 2 This embodiment provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 4 nm and a pore volume of 0.85 cm³ were prepared. 3 / g, specific surface area 1800m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min; (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Adjust the temperature to 500℃, and pass a mixture of 5% ethylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for surface carbon coating treatment for 2h, and cool to room temperature to obtain silicon-carbon material. (4) Dissolve 1.111g lithium nitrate and 4.415g ammonium dihydrogen phosphate in 300ml of water to obtain the first solution; dissolve 10.436g zirconium nitrate pentahydrate and 0.328g magnesium nitrate hexahydrate in 200ml of water to obtain the second solution; (5) Add 200g of the silicon-carbon material obtained in step (3) to the first solution and stir at high speed for 1 hour to form a suspension; (6) The second solution is slowly added dropwise to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor was calcined at 850°C for 4 hours under a nitrogen atmosphere at a heating rate of 3°C / min, and then allowed to cool naturally to obtain Li. 1.2 Mg 0.1 Zr 1.9 (PO4)3 coated silicon-carbon anode material.

[0028] A method for preparing an all-solid-state lithium battery: as described in Example 1.

[0029] Example 3 This embodiment provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 4 nm and a pore volume of 0.85 cm³ were prepared. 3 / g, specific surface area 1800m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min; (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Keep the temperature at 600℃, and pass a mixture of 5% propylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for 2 hours to perform surface carbon coating treatment. Cool to room temperature to obtain silicon-carbon material. (4) Dissolve 1.105g lithium nitrate and 4.473g ammonium dihydrogen phosphate in 300ml of water to obtain the first solution; dissolve 10.018g zirconium nitrate pentahydrate and 0.973g aluminum nitrate nonahydrate in 200ml of water to obtain the second solution; (5) Add 200g of the silicon-carbon material obtained in step (3) to the first solution and stir at high speed for 1 hour to form a suspension; (6) The second solution is slowly added dropwise to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor was calcined at 650°C for 4 hours under a nitrogen atmosphere at a heating rate of 3°C / min, and then allowed to cool naturally to obtain Li. 1.2 Al 0.2 Zr 1.8 (PO4)3 coated silicon-carbon anode material.

[0030] A method for preparing an all-solid-state lithium battery: as described in Example 1.

[0031] Example 4 This embodiment provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 4 nm and a pore volume of 0.85 cm³ were prepared. 3 / g, specific surface area 1800m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min. (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Keep the temperature at 600℃, and pass a mixture of 5% propylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for 2 hours to perform surface carbon coating treatment. Cool to room temperature to obtain silicon-carbon material. (4) Dissolve 0.396g lithium hydroxide and 4.400g ammonium dihydrogen phosphate in 300ml of water to obtain the first solution; dissolve 5.602g zirconium oxynitrate and 0.168g calcium nitrite in 200ml of water to obtain the second solution; (5) Add 200g of the silicon-carbon material obtained in step (3) to the first solution and stir at high speed for 1 hour to form a suspension; (6) The second solution is slowly added dropwise to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor was calcined at 850°C for 7 hours under a nitrogen atmosphere at a heating rate of 5°C / min, and then allowed to cool naturally to obtain Li. 1.2 Ca 0.1 Zr 1.9 (PO4)3 coated silicon-carbon anode material.

[0032] A method for preparing an all-solid-state lithium battery: as described in Example 1.

[0033] Example 5 This embodiment provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 4 nm and a pore volume of 0.85 cm³ were prepared. 3 / g, specific surface area 1800m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min. (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Keep the temperature at 600℃, and pass a mixture of 5% propylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for 2 hours to perform surface carbon coating treatment. Cool to room temperature to obtain silicon-carbon material. (4) Dissolve 0.996g lithium nitrate and 5.593g ammonium phosphate in 300ml of water to obtain the first solution; dissolve 10.201g zirconium nitrate pentahydrate and 0.406g lanthanum nitrate in 200ml of water to obtain the second solution; (5) Add 200g of the silicon-carbon material obtained in step (3) to the first solution and stir at high speed for 1 hour to form a suspension; (6) The second solution is slowly added dropwise to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor was calcined at 700°C for 12 hours under a nitrogen atmosphere with a heating rate of 5°C / min. After natural cooling, Li was obtained. 1.1 La 0.1 Zr 1.9 (PO4)3 coated silicon-carbon anode material.

[0034] A method for preparing an all-solid-state lithium battery: as described in Example 1.

[0035] Comparative Example 1 This comparative example provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 4 nm and a pore volume of 0.85 cm³ were prepared. 3 / g, specific surface area 1800m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min; (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Adjust the temperature to 500℃, and pass a mixture of 5% ethylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for 2 hours to perform surface carbon coating treatment. Cool to room temperature to obtain silicon-carbon anode material.

[0036] A method for preparing an all-solid-state lithium battery: as described in Example 1.

[0037] Comparative Example 2 This comparative example provides a method for preparing silicon-carbon anode materials: (1) Under an inert atmosphere, an average pore size of 4 nm and a pore volume of 0.85 cm³ were prepared. 3 / g, specific surface area 1800m² 2 / g of porous carbon material was placed in a deposition furnace and heated to 600℃ at a rate of 10℃ / min; (2) Silicane gas was introduced at a flow rate of 5 L / min and vapor deposition was carried out for 4 h to form nano-silicon particles; (3) Adjust the temperature to 500℃, and pass a mixture of 5% ethylene and 95% nitrogen into the deposition furnace at a flow rate of 5L / min for surface carbon coating treatment for 2h, and cool to room temperature to obtain silicon-carbon material. (4) Dissolve 8g of lithium nitrate and 4.415g of ammonium dihydrogen phosphate in 300ml of water to obtain the first solution; (5) Add 200g of the silicon-carbon material obtained in step (3) to the first solution and stir at high speed for 1 hour to form a suspension; (6) The suspension obtained in step (5) is spray-dried to obtain a powder precursor; and (7) The powder precursor was calcined at 850°C for 4 hours under a nitrogen atmosphere with a heating rate of 3°C / min. After natural cooling, Li3PO4-coated silicon-carbon anode material was obtained.

[0038] A method for preparing an all-solid-state lithium battery: as described in Example 1.

[0039] Performance testing Battery testing conditions: Test voltage range -0.65V to 1V (vs. Li + The silicon-carbon anode material ( / Li) was subjected to rate testing by switching the current between 0.1C, 0.5C, 1C, and 2C. Cyclic testing was then performed at a current rate of 0.5C for 200 cycles. The test results are shown in Table 1. Simultaneously, silicon-carbon anode materials coated with carbon or Li3PO4 were used as comparative experiments.

[0040] Table 1 Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A silicon-carbon anode material, characterized in that, The silicon-carbon anode material comprises a porous carbon framework, nano-silicon particles dispersed in the porous carbon framework, a carbon layer deposited on the porous carbon surface of the dispersed nano-silicon particles, and a fast-ion conductor coating layer on the carbon layer, wherein the fast-ion conductor has the chemical formula LiZr2(PO4)3 or Li y M x Zr 2-x (PO4)3, where M = Al, La, Ca or Mg, 0≤x≤0.2, 1≤y≤1.

4.

2. The silicon-carbon anode material according to claim 1, characterized in that, The amount of the fast ion conductor coating is 0.01 wt% to 10 wt% based on the total weight of the silicon-carbon anode material.

3. The silicon-carbon anode material according to claim 1 or 2, characterized in that, The thickness of the fast ion conductor coating is 10 nm-200 nm.

4. A method for preparing a silicon-carbon anode material according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Under an inert atmosphere, the porous carbon material used as the substrate is placed in a deposition furnace and heated to 400℃-800℃; (2) Silicon source gas is introduced into the deposition furnace for vapor phase deposition to form nano-silicon particles; (3) Adjust the temperature to 300℃-800℃, introduce the mixed gas containing carbon source gas and carrier gas into the deposition furnace for surface carbon coating treatment, and cool to room temperature to obtain silicon carbide material. (4) Dissolve lithium salt and phosphate in water according to the stoichiometric ratio to obtain the first solution, wherein lithium salt is in excess; A second solution is obtained by dissolving zirconium salt, or zirconium salt and other non-zirconium metal salts, in water according to stoichiometric ratio; (5) The silicon-carbon material obtained in step (3) is added to the first solution and dispersed by high-speed stirring to obtain a suspension; (6) Add the second solution to the suspension obtained in step (5) under high-speed stirring; (7) The suspension obtained in step (6) is spray-dried to obtain a powder precursor; and (8) The powder precursor is calcined in an inert atmosphere and naturally cooled to obtain a silicon-carbon anode material coated with a fast ion conductor.

5. The method according to claim 4, characterized in that, In step (1), the porous carbon material has a pore size of 1 nm-10 nm and a pore volume of 0.5 cm³. 3 / g-1.2cm 3 / g, specific surface area is 400m² 2 / g-2000m 2 / g.

6. The method according to claim 4, characterized in that, In step (2), the silicon source gas is selected from one or more of silane, silane, dichlorosilane, and trichlorosilane; The flow rate of the silicon source gas is 0.1 L / min - 50 L / min; and / or The vapor deposition time is 2h-16h.

7. The method according to claim 4, characterized in that, In step (3), the carbon source gas is one or more of methane, ethane, ethylene, propane, propylene, and propyne; The carrier gas is an inert gas, optionally nitrogen; The volume ratio of the carbon source gas is 1%-10%, and the volume ratio of the carrier gas is 90%-99%. The flow rate of the mixed gas is 0.1 L / min - 50 L / min; and / or The carbon coating time is 0.5h-6h.

8. The method according to any one of claims 4-7, characterized in that, In step (4), the lithium salt is one or both of lithium nitrate and lithium hydroxide; The phosphate is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; The zirconium salt is zirconium nitrate or zirconium oxynitrate; The other non-zirconium metal salts mentioned are one or more of aluminum nitrate, lanthanum nitrate, calcium nitrate, calcium nitrite, and magnesium nitrate; and / or The excess lithium salt ranges from 2wt% to 10wt%.

9. The method according to any one of claims 4-7, characterized in that, In step (8), the inert atmosphere is one or both of nitrogen and argon; The calcination temperature is 600℃-900℃. Calcination time is 1h-24h, and / or The heating rate is 1℃ / min-10℃ / min.

10. An all-solid-state lithium battery, the all-solid-state lithium battery comprising a negative electrode, characterized in that, The negative electrode comprises the silicon-carbon negative electrode material according to any one of claims 1-3 or the silicon-carbon negative electrode material prepared by the method according to any one of claims 4-9.